Literary Research in a Peruvian University: A Systematic Mapping of Undergraduate Theses - Núñez-Núñez , Marianné; Guillén-Chávez, Evelyn-Paola; Sánchez-Gómez, Mª Cruz (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This study aims to analyse undergraduate research in Literature at a Peruvian university. A systematic mapping of ten works published between 2017 and 2022 was carried out. The results show a preference for research in Peruvian literature and that the most studied literary genre is narrative. It is concluded that the studies do not clearly describe scientific methods or methodologies of literary analysis; due to their diversity, to the fact that literary studies have an interdisciplinary complexity, and because university educational efforts in research are focused on the last semesters.